Побудова моделі динаміки виробничо-ринкових процесів у двосекторній макроекономіці - Pankratova, Nataliya D.; Khoroshun, L. P.; Yakhin, S. L. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A mathematical model of the dynamics of production-market processes in macroeconomics is proposed, which is based on the associated differential equations of the production balance taking into account productivity, depreciation of production accumulation and human participation, and the balance of monetary flows in a two-sector macroeconomy model with extended reproduction. A generalization of the production model in the case of the existence of types of capital with different productivity, production accumulation, depreciation and participation of people has been carried out. The specific tasks describing the growth, decline and cyclical nature of production, as well as inflation, are considered.